The Role of Leadership in Fostering Employee Engagement: A Literature Analysis - Ramlan, Muchsin; Akob, Muh; Jumady, Edy (Manunggal Halim Jaya, 2025)
The primary objective of this research is to explore the critical role of leadership in fostering sustained employee engagement. By examining transformational, transactional, and servant leadership styles, this study seeks to identify the mechanisms through which these leadership approaches influence employee engagement. A qualitative literature review method was employed, involving a comprehensive analysis of peer-reviewed journal articles, books, and reputable online sources. The findings indicate that transformational leadership significantly enhances employee engagement through vision articulation, inspirational motivation, intellectual stimulation, and individualized consideration. Transactional leadership, with its emphasis on clear goals, feedback, and rewards, provides necessary structure and stability, particularly in regulated industries. Servant leadership, focusing on ethical behavior and community building, fosters trust, collaboration, and mutual respect, leading to higher engagement levels. The study also highlights key mechanisms such as emotional intelligence, effective communication, feedback, and organizational support as critical factors enabling leaders to create supportive and engaging work environments. Empirical evidence supports the positive impact of these leadership styles on employee engagement, underscoring their relevance in contemporary organizational contexts. Future research should further explore contextual factors, long-term effects, technological mediation, and diversity, equity, and inclusion (DEI) considerations to enhance the understanding of the leadership-engagement nexus. The insights gained from this study can help organizations develop targeted leadership programs that promote high levels of engagement, ultimately leading to improved organizational performance and employee satisfaction.